AB1044 CYTOKINE PROFILE OF MACROPHAGE ACTIVATION SYNDROME ASSOCIATED WITH KAWASAKI DISEASE. (June 2019) - Sakumura, Naoto; Shimizu, Masaki; Jinkawa, Asumi; Irabu, Hitoshi; Takakuwa, Maiko; Inoue, Natsumi; Mizuta, Mao; Yachie, Akihiro
Abstract : Background: Macrophage activation syndrome (MAS) is a severe, potentially life-threatening complication of childhood systemic inflammatory disorders. MAS occurs most often in children with systemic juvenile idiopathic arthritis and less commonly in children with Kawasaki disease (KD). Objectives: Our study aimed to assess the kinetics of cytokine release and compare the accuracy of serum biomarkers for diagnosis of MAS, including neopterin, IL-18, IL-6 and soluble TNF receptor type I (sTNFR-I) and sTNFR-II levels, we analysed these levels in patients with KD, including those with MAS, and compared them to the clinical features of KD and MAS. Methods: Serum neopterin, interleukin (IL)-18, IL-6 and soluble tumour necrosis factor receptor type I (sTNFR-I) and sTNFR-II levels were determined using enzyme-linked immunosorbent assay in 78 patients with KD, including five with MAS. Results were compared to the clinical features of MAS. Results: Serum neopterin, IL-18, sTNFR-II levels and sTNFR-II/I ratio were significantly elevated in KD patients with MAS compared to those in the acute phase. Receiver operating characteristic curve analysis revealed areas under the curve and cutoff values of neopterin, IL-18, sTNFR-II levels and sTNFR-II/I ratio were 0.9750/30.0 nmol/L, 0.9813/1165 ng/mL, 0.9969/16, 600 pg/mL and 0.9875/4.475, respectively. Serum sTNFR-II levels correlated positively with disease activity. Conclusion: These findings indicate that interferon (IFN)–γ and tumour necrosis factor-α (TNF-α) are closely associated with the pathogenesis of MAS associated with KD. Serum sTNFR-II levels might be a useful marker to diagnose the transition to MAS. References: [1] García-Pavón S, et al. J Pediatr Hematol Oncol 2017;39:445-451. [2] Shimizu M, et al. Cytokine 2018;108:168-172. Disclosure of Interests: None declared